The syncretic image of a saint in The Life of Saint Cuthbert by Saint Bede the Venerable - Zelezinskaya, Natalia S. (Journal of the Belarusian State University. Philology, 2023)
The study considers the image of a saint in the work of early English hagiography (Vita Sancti Cuthberti by Saint Bede the Venerable) to show a syncretic structure of this image. It combines the features of an epic hero, an ascetic, a hermit, a wonder worker, a visionary, a bishop, and a martyr. Its syncretic nature is explained by Saint Bede the Venerable’s attempt to involve the tradition of Celtic (Irish) Church of accepting pagan folklore and mythic sources, to tell the story of a real English monk, to follow the Roman canon of hagiographic genre (after the Synod of Whitby of 664) and the example of Gospels as a prototype of hagiography. Syncretism is observed on semantic, structural, and paradigmatic levels of the image. The article dwells upon the composition, the author’s intentions and the style. The relevant religious, cultural, political, and literary contexts are touched upon. Saint Bede the Venerable’s sources are mentioned to show that the author’s purpose was to tell his brethren about a real man and about the ideal of the age as the Roman Church saw it. His conflicting intentions are reflected in the motives of the life. Much attention is paid to the motives of prophecy, help, hermitage, wonders, piety, love, death as well as to the vision as a motive (and potentially a genre). The methodology of historical poetics by A. N. Veselovsky provides the research with both paradigmatic and syntagmatic dimensions. The image of a saint in Saint Bede the Venerable interpretation is one of the most influential images of English literature (both religious and civil) since the 8th century until now. This is the first study on English hagiography conducted in Belarus.
Keywords: life (vita); hagiography; hagiology; the image of a saint; the motive of sanctity; syncretic image; Saint Bede the Venerable; Saint Cuthbert; English medieval literature; historical poetics; the history of ideas; A. N. Veselovsky